If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3n + 4) = 2(6n + 8) Reorder the terms: 4(4 + 3n) = 2(6n + 8) (4 * 4 + 3n * 4) = 2(6n + 8) (16 + 12n) = 2(6n + 8) Reorder the terms: 16 + 12n = 2(8 + 6n) 16 + 12n = (8 * 2 + 6n * 2) 16 + 12n = (16 + 12n) Add '-16' to each side of the equation. 16 + -16 + 12n = 16 + -16 + 12n Combine like terms: 16 + -16 = 0 0 + 12n = 16 + -16 + 12n 12n = 16 + -16 + 12n Combine like terms: 16 + -16 = 0 12n = 0 + 12n 12n = 12n Add '-12n' to each side of the equation. 12n + -12n = 12n + -12n Combine like terms: 12n + -12n = 0 0 = 12n + -12n Combine like terms: 12n + -12n = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 | | 16-s=20 |